1983
DOI: 10.1111/j.1439-0329.1983.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence and accumulation of fungitoxic substances against Ceratocystis ulmi in Ulmus americana: possible relation to induced resistance1

Abstract: This paper reports the differential accumulation of inhibitory compounds in American elm seedlings after inoeulation with a non-aggressive and an aggressive strain of C. ulmi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…On elm metabolites toxic to O. ulmi, or enzymes that may degrade its cell walls, not too many data are known. JENG et al (1983) suggested an important role for several phytoalexins they found in U. americana after inoculation with a non-aggressive isolate of O. uimi followed by inoculation with an aggressive one. These compounds may play a role in restricting growth of O. ulmi, but the two phytoalexins mansonone E and F, that in another study were found to constitute the bulk of the fungitoxic material produced in elm, were not very toxic to O.…”
Section: Discussionmentioning
confidence: 88%
“…On elm metabolites toxic to O. ulmi, or enzymes that may degrade its cell walls, not too many data are known. JENG et al (1983) suggested an important role for several phytoalexins they found in U. americana after inoculation with a non-aggressive isolate of O. uimi followed by inoculation with an aggressive one. These compounds may play a role in restricting growth of O. ulmi, but the two phytoalexins mansonone E and F, that in another study were found to constitute the bulk of the fungitoxic material produced in elm, were not very toxic to O.…”
Section: Discussionmentioning
confidence: 88%
“…Other environmental factors, such as the chemical environment (Martín et al 2008b(Martín et al , 2010aVivas et al 2012) or the action of less aggressive Ophiostoma strains inducing tree resistance (Hubbes and Jeng 1981;Jeng et al 1983) should not be discarded as factors involved in environmental resistance. A deeper study of the fungal microbiome and its spatial distribution over the tree architecture, including seeds, could help to identify candidate mutualistic endophytes in elms.…”
Section: Resultsmentioning
confidence: 98%
“…Reactions taking place as a consequence of the infection may be both anatomical and chemical, and they represent a second inducible defense strategy. These reactions include blockage of vessels by tyloses, embolisms, accumulation of pectic and hemicellulosic substances (Elgersma 1982, Shigo 1982, Ouellette & Rioux 1992, Rioux et al 1998, formation of chemicals, such as phytoalexin-like sesquiterpenes (Jeng et al 1983, Duchesne et al 1985, Sticklen et al 1991, and histological barriers typically containing phenolic compounds and suberin (Rioux & Ouellette 1991a, Rioux & Ouellette 1991b, Ouellette et al 2004a, Ouellette et al 2004b, Et-Touil et al 2005.…”
Section: Box 1 -Glossarymentioning
confidence: 99%